If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -24 = x Reorder the terms: -24 + 4x = x Solving -24 + 4x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -24 + 4x + -1x = x + -1x Combine like terms: 4x + -1x = 3x -24 + 3x = x + -1x Combine like terms: x + -1x = 0 -24 + 3x = 0 Add '24' to each side of the equation. -24 + 24 + 3x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 3x = 0 + 24 3x = 0 + 24 Combine like terms: 0 + 24 = 24 3x = 24 Divide each side by '3'. x = 8 Simplifying x = 8
| 0.66X-4=3X-1+(4x+3) | | 5+2ln^2= | | 8-3X=6X+7 | | 3d-1=10 | | 4x+6y=1788 | | 6b^2+5b=1 | | 4x-3=11x+5 | | 3(x-2)=5(3x-2) | | 3x+1=9-5x | | 3w+36=4w-18 | | 3(k+7)=75 | | x^5+2x^2=0 | | 5a+2(3a+4)-2a= | | 2b^2-3b=5 | | N=55000-2000x | | 7v-5=4v+4 | | 3(v+4)+v=20 | | 5x-5+6-3x=0 | | q*4q*5q= | | 5(2y+10)=110 | | 3x+2y-z=23 | | 3-5x=4+2x | | X^4-3x^2-x^3+4x-4=0 | | x=6.25+0.25y+-0.5z | | 5(x+6)+2=37 | | 3(x+1)-x+4=2x+8 | | 282-10x=20x+12 | | z^3-i*z^2+4z-4i=0 | | x^4-7x^3+7x^2+42x+63=0 | | 4(x+12)+2(x+18)=-6 | | x^4+11x^3+7x^2+42x+63=0 | | x^4+6x^3+7x^2+42x+63=0 |